2019
DOI: 10.1152/ajpheart.00685.2018
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis lethal toxin, but not edema toxin, increases pulmonary artery pressure and permeability in isolated perfused rat lungs

Abstract: Although lethal toxin (LT) and edema toxin (ET) contribute to lethality during Bacillus anthracis infection, whether they increase vascular permeability and the extravascular fluid accumulation characterizing this infection is unclear. We employed an isolated perfused Sprague-Dawley rat lung model to investigate LT and ET effects on pulmonary vascular permeability. Lungs ( n ≥ 6 per experimental group) were isolated, ventilated, suspended from a force transducer, and perfused. Lung weight and pulmonary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Patients progressing to severe anthrax infection have extensive extravascular fluid accumulation manifested as pleural and peritoneal effusions and tissue edema [4,17,46,47]. Even though evidence suggests that lethal toxin disrupts endothelial barrier function, PGN-stimulated intravascular inflammation and coagulopathy could also contribute to this endothelial dysfunction [46,48,49]. Such inflammation is known to disrupt endothelial gap junction function and allows extravasation of protein and fluid [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Patients progressing to severe anthrax infection have extensive extravascular fluid accumulation manifested as pleural and peritoneal effusions and tissue edema [4,17,46,47]. Even though evidence suggests that lethal toxin disrupts endothelial barrier function, PGN-stimulated intravascular inflammation and coagulopathy could also contribute to this endothelial dysfunction [46,48,49]. Such inflammation is known to disrupt endothelial gap junction function and allows extravasation of protein and fluid [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…To review the pathogenicity of anthrax toxins to lungs at the cellular level, it may be more appropriate to discuss each of the toxins (LeTx and EdTx) separately. Accordingly, it has been shown in a model of isolated perfused rat lungs that they have different impacts on pulmonary vascular pressures and permeability [288]. However, in vivo studies revealed that these toxin components may cooperate synergistically to cause edema formation and cell death.…”
Section: Anthrax Toxinsmentioning
confidence: 99%
“…Thus, the concerted action of the two should not be overlooked in practice [289]. It has been shown in vitro and in vivo that LeTx creates most characteristics of an anthrax infection including cytokine-independent vascular dysregulation and collapse, pulmonary vascular constriction, disruption of the rat pulmonary microvascular endothelial barrier integrity leading to severe blood vessel leakage, pulmonary edema, and disrupted gas exchange that clinically leads to ALI/ARDS [275,288,[290][291][292][293][294].…”
Section: Anthrax Toxinsmentioning
confidence: 99%